MicroRNAs as Biomarkers and Therapeutic Targets in Doxorubicin-Induced Cardiomyopathy: A Review - Chen, Liuying; Xu, Yizhou (Frontiers in Cardiovascular Medicine, 2021)
Doxorubicin is a broad-spectrum chemotherapy drug applied in antitumor therapy. However, its clinical utility is limited by its fatal cardiotoxicity. Doxorubicin (DOX)-induced cardiomyopathy (DIC) begins with the first DOX dose and is characterized by being cumulative dose-dependent, and its early diagnosis using common detection methods is very difficult. Therefore, it is urgent to determine the underlying mechanism of DIC to construct treatment strategies for the early intervention before irreversible damage to the myocardium occurs. Growing evidence suggests that microRNAs (miRNAs) play regulatory roles in the cardiovascular system. miRNAs may be involved in DIC by acting through multiple pathways to induce cardiomyocyte injury. Recent studies have shown that the dysregulation of miRNA expression can aggravate the pathological process of DIC, including the induction of oxidative stress, apoptosis, ion channel dysfunction and microvascular dysfunction. Current findings on the roles of miRNAs in DIC have led to a wide range of studies exploring candidate miRNAs to be utilized as diagnostic biomarkers and potential therapeutic targets for DIC. In this review, we discuss frontier studies on the roles of miRNAs in DIC to better understand their functions, develop relevant applications in DIC, discuss possible reasons for the limitations of their use and speculate on innovative treatment strategies.